(untitled) (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: Patient preference for their doctor’s attire can influence their assessment of the quality of care. Most patients prefer specialists and hospital-based physicians to wear white coats, but evidence from general practitioner (GP) practices is lacking. We aimed to assess patient preference for GPs to wear white coats in Switzerland. METHODS: We conducted a cross-sectional survey in the canton of Geneva, Switzerland, in 2011. The survey was part of a larger study on patient expectations from their GP. A random sample of 75 GPs was contacted by post and 23 agreed to participate. They were asked to recruit between 50 and 100 consecutive patients coming to the practice for a scheduled consultation. Patients were asked to complete a questionnaire on their expectations from the GP, including whether they preferred their GP to wear a white coat or not. RESULTS: 1,637 patients agreed to participate (participation rate: 97%, women: 63%, mean age: 64 years). Overall, wearing a white coat was considered important by only 34% of participants. In multivariate analyses, older patients, those of Italian background and patients consulting uncertified GPs and/or GPs wearing a white coat were more likely to consider white coats as being important. CONCLUSIONS: These findings suggest that white coats are no longer considered a powerful symbol for a large majority of patients visiting GPs. However, GPs may wish to adjust their attire to meet the expectations of their more conservative patients.